2016
DOI: 10.3928/01477447-20160222-04
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Specific Femoral Short Stems and Conventional-Length Stems in Primary Cementless Total Hip Arthroplasty

Abstract: There are several reported disadvantages with conventional-length femoral stems in cementless total hip arthroplasty (THA). Therefore, various efforts have been made to develop a specific femoral short stem to improve physiologic bone remodeling at the femoral aspect of a cementless THA. However, there are potential disadvantages with specific femoral short stems, such as malalignment, inadvertent subsidence, and potential proximal femoral fracture. Therefore, the authors quantitatively compared radiographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 28 publications
0
55
0
Order By: Relevance
“…[ 24 25 ] A pooled analysis of the data showed a low incidence of thigh pain in SSs when comparing with CSs, and several studies have demonstrated the low incidence of thigh pain with SSs, [ 21 26–28 ] which can be attributed to the design of the femoral stem. Shin et al [29] also reported that a lower incidence of thigh pain in SSs than in CSs. An SS can reduce proximal stress shielding through diaphyseal fixation of the femoral stem and the development of excellent mechanical transmission.…”
Section: Discussionmentioning
confidence: 93%
“…[ 24 25 ] A pooled analysis of the data showed a low incidence of thigh pain in SSs when comparing with CSs, and several studies have demonstrated the low incidence of thigh pain with SSs, [ 21 26–28 ] which can be attributed to the design of the femoral stem. Shin et al [29] also reported that a lower incidence of thigh pain in SSs than in CSs. An SS can reduce proximal stress shielding through diaphyseal fixation of the femoral stem and the development of excellent mechanical transmission.…”
Section: Discussionmentioning
confidence: 93%
“…McCalden et al 19 SMF Synergy Lateral Meyer et al 5 Fitmore CLS straight Lateral Salemyr et al 20 Proxima Bimetric Posterolateral Schilcher et al 21 Taperloc Microplasty Taperloc Posterior Sluimer et al 22 Omnifit-HA 1090 Omnifit-HA 1017 Posterolateral van Oldenrijk et al 23 CFP Zweymuller Lateral von Roth et al 24 Fitmore CLS Anterolateral S, short stem; C, conventional stem. 32 Retrospective Short Citation Multiple Posterolateral Shin et al 33 Prospective Metha Bicontact Posterolateral Tahim et al 34 Retrospective Microtaperloc Taperloc Posterior Tomazewski et al 35 Prospective Proxima ABG II Anterolateral + Posterolateral No data Yu et al 36 Retrospective Tri-locked stem Corail Posterolateral…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Individually all 4 showed no statistical difference in HHS between short and conventional stems. 22,25,28,33 Therefore, 17 studies presented the necessary data for meta-analysis, representing 1926 total hip replacements. A random effects model was applied as heterogeneity testing revealed an I 2 value of 52%.…”
Section: Comparison Of Harris Hip Scoresmentioning
confidence: 99%
“…Shin et al 39 compared the METHA stem with a conventional-length femoral stem (BiCONTACT, Aesculap) including 50 hips in each group matched for age, sex, body mass index (BMI), height, surgical approach and surgeon. The authors did not find significant differences between the two groups in terms of post-operative radiographic outcomes, functional outcomes or complications.…”
Section: Stem Features and Outcomesmentioning
confidence: 99%